Modeling autoregulation of cardiac excitation-Ca-contraction and arrhythmogenic activities in response to mechanical load changes - Asuka Hatano; Leighton T. Izu; Ye Chen-Izu; Daisuke Sato (iScience)
Summary: The heart has intrinsic abilities to autoregulate contractile force in response to mechanical load. Recent experimental studies show that cardiomyocytes have mechano-chemo-transduction (MCT) mechanisms that form a closed feedback loop in the excitation-Ca2+ signaling-contraction (E-C) coupling. This closed feedback loop enables autoregulation of contraction in response to mechanical load changes. Here, we develop the first autoregulatory E-C coupling model that couples electrophysiology, Ca2+ signaling, force development and contraction, and MCT feedback. The model recapitulates the experimental data showing that the mechanical load on cardiomyocytes during contraction increases the L-type Ca2+ current, action potential duration, sarcoplasmic reticulum (SR) Ca2+ content, and SR Ca2+ release, giving rise to increased cytosolic Ca2+ transient (MCT-Ca2+ gain) and enhanced contraction. The model also makes non-trivial predictions on the autoregulation of contraction with moderate MCT-Ca2+ gain under a range of physiological load changes, but arrhythmogenic discordant alternans with excessive MCT-Ca2+ gain under pathological overload.